Ground-based hyperspectral remote sensing for weed management in crop production - Huang, Yanbo; Lee, Matthew A.; Thomson, Steven J.; Reddy, Krishna N. (International Journal of Agricultural and Biological Engineering, 2016)
Agricultural remote sensing has been developed and applied in monitoring soil, crop growth, weed infestation, insects, diseases and water status in farm fields to provide data and information to guide agricultural management practices. Precision agriculture has been implemented through prescription mapping of crop fields at different scales with the data remotely sensed from space-borne, airborne and ground-based platforms. Ground-based remote sensing techniques offer portability, flexibility and controllability in applications for precision agriculture. In weed management, crop injury from off-target herbicide spray drift and herbicide resistance in weeds are two important issues. For precision weed management, ground-based hyperspectral remote sensing techniques were developed for detection of crop injury from dicamba and differentiation between glyphosate resistant and sensitive weeds. This research presents the techniques for ground-based hyperspectral remote sensing for these two applications. Results illustrate the advantages of ground-based hyperspectral remote sensing for precision weed management. Keywords: ground-based remote sensing, hyperspectral, crop injury, herbicide resistance, precision agriculture DOI: 10.3965/j.ijabe.20160902.2137 Citation: Huang Y, Lee M A, Thomson S J, Reddy K N. Ground-based hyperspectral remote sensing for weed management in crop production. Int J Agric & Biol Eng, 2016; 9(2): 98-109.